Activation of Follicle-Stimulating Hormone Receptor in Adrenal Zona Fasciculata Cells Promotes Cortisol Secretion: Implications for the Development of Menopause-Associated Diseases - Wu, Jing-Gen; Zhao, Peng; Yang, Jing; Wang, Ming-Juan; Chen, Jian-Hua; Li, Xiao-Yong; Ying, Xue; Lu, Yong-Chao (Experimental and Clinical Endocrinology & Diabetes, 2024)
Objective Changes in postmenopausal hormone levels are associated with a variety of disorders. This study elucidated the mechanism by which follicle-stimulating hormone (FSH) increases cortisol production involved in development of menopause-related diseases.Methods The expression of FSH receptors (FSHRs) in murine adrenal zona fasciculata (AZF) cells and ATC7 cells was verified by immunofluorescence, western blotting and RT–PCR. The function of FSHR in promoting cortisol production was analyzed by cell culture and molecular biological methods. FSHR signaling pathways in ATC7 cells were analyzed by ELISA, qRT–PCR, and western blotting. Further, a mouse model was established by ovariectomy. Ovariectomized mice were treated with GnRHa. Ovariectomized mice initially received physiological doses of estrogen and were then injected with recombinant FSH. Then serum FSH, luteinizing hormone (LH), estradiol, and cortisol, and bone mineral density (BMD), blood pressure (BP) and heart rate (HR) were determined.Results FSHRs were expressed in murine AZF cells and ATC7 cells. FSH accelerated cortisol production through activated protein kinase A (PKA), cyclic adenosine monophosphate (cAMP)-response element binding protein (CREB), protein kinase B (PKB/AKT) and 5ʼ AMP-activated protein kinase (MAPK) signaling pathways by Gsα-coupled FSHRs in ATC7 cells. Serum FSH levels (P<0.001) were elevated in ovariectomized mice with concurrent increases in cortisol (P<0.01), areal BMD (aBMD) (P<0.05), volumetric BMD (vBMD) (P<0.05), systolic BP (SBP) (P<0.05), diastolic BP (DBP) (P<0.05), and HR (P<0.05). However, the administration of GnRHa suppressed the increase in FSH levels and the elevation of cortisol, aBMD, vBMD, SBP, DBP, and HR induced by ovariectomy, even in the presence of normal serum estradiol levels.Conclusion The study findings indicate that elevated FSH levels stimulate cortisol secretion, through a mechanism related to FSHRs expression in AZF cells.
Keywords: follicle-stimulating hormone receptor; adrenal zona fasciculata cells; cortisol; menopause; ovariectomy